2019
DOI: 10.1002/mp.13496
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of registration algorithms in subtraction CT of the lungs: A digital phantom study

Abstract: Purpose The purpose of this study was to assess, using an anthropomorphic digital phantom, the accuracy of algorithms in registering precontrast and contrast‐enhanced computed tomography (CT) chest images for generation of iodine maps of the pulmonary parenchyma via temporal subtraction. Materials and methods The XCAT phantom, with enhanced airway and pulmonary vessel structures, was used to simulate precontrast and contrast‐enhanced chest images at various inspiration levels and added CT simulation for realis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
(44 reference statements)
0
2
0
Order By: Relevance
“…In contrast to DECT for the ADCT system, pulmonary perfusion evaluation for ADCT has been made possible by use of the subtraction technique with the appropriate software [78][79][80][81][82][83][84]. An in vitro study demonstrated that the contrast-to-noise ratio (CNR) of subtraction ADCT was superior to that of DECT by assessment with different iodine contrast media phantoms [79,80], while another in vivo study confirmed the superior clinical potential of subtraction ADCT in comparison with that of CE-CT pulmonary angiography (CE-CTPA) or DECT [81][82][83]. Moreover, lung subtraction iodine mapping by subtraction ADCT was shown to perform significantly better than CE-CTPA for patients with chronic thromboembolic pulmonary hypertension (CTEPH) [82].…”
Section: Subtraction Adctmentioning
confidence: 99%
“…In contrast to DECT for the ADCT system, pulmonary perfusion evaluation for ADCT has been made possible by use of the subtraction technique with the appropriate software [78][79][80][81][82][83][84]. An in vitro study demonstrated that the contrast-to-noise ratio (CNR) of subtraction ADCT was superior to that of DECT by assessment with different iodine contrast media phantoms [79,80], while another in vivo study confirmed the superior clinical potential of subtraction ADCT in comparison with that of CE-CT pulmonary angiography (CE-CTPA) or DECT [81][82][83]. Moreover, lung subtraction iodine mapping by subtraction ADCT was shown to perform significantly better than CE-CTPA for patients with chronic thromboembolic pulmonary hypertension (CTEPH) [82].…”
Section: Subtraction Adctmentioning
confidence: 99%
“…In order to evaluate the potential impact of the difference in diaphragm level between the pre-contrast and contrast-enhanced CT on the visibility of the nodule enhancement in subtraction CT, a subset of all scans with a diaphragm level difference larger than 6.0 mm was selected. This threshold was used since this had been found to be the average difference in the clinical setting [13].…”
Section: Observer Studymentioning
confidence: 99%
“…Subtraction CT is a recently introduced technique that generates iodine maps of the lungs by subtracting a pre-contrast CT from a contrast-enhanced CT after motion correction [12]. Even with differences in inspiration between the two scans, the iodine enhancement maps with this technique have been shown to be accurate for detection of perfusion defects in the pulmonary parenchyma, with similar diagnostic performance as dual-energy CT [13,14]. However, perfusion defects are relatively large, usually in the centimeter range, while pulmonary nodules of clinical interest are as small as 4 mm [3].…”
Section: Introductionmentioning
confidence: 99%